2017
DOI: 10.1186/s13256-017-1384-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glomerular basement membrane glomerulonephritis following nintedanib for idiopathic pulmonary fibrosis: a case report

Abstract: BackgroundWe report a previously unrecognized and unreported case of a patient with anti-glomerular basement membrane glomerulonephritis following nintedanib, an orally active small molecule tyrosine kinase inhibitor.Case presentationA 59-year-old Caucasian woman with a history of idiopathic pulmonary fibrosis presented with severe acute kidney injury (creatinine 285 umol/L) secondary to anti-glomerular basement membrane glomerulonephritis disease 4 months after commencement of nintedanib. She had hematuria wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Endothelial dysfunction is hypothesized to be a potential cause of proteinuria ( 6 ). While there have been a few reports of nintedanib being used to treat idiopathic pulmonary fibrosis, inducing anti-glomerular basement membrane disease, and renal thrombotic microangiopathy ( 7 , 8 ), the renal pathology in our patient did not exhibit either of these conditions.…”
Section: Discussioncontrasting
confidence: 65%
“…Endothelial dysfunction is hypothesized to be a potential cause of proteinuria ( 6 ). While there have been a few reports of nintedanib being used to treat idiopathic pulmonary fibrosis, inducing anti-glomerular basement membrane disease, and renal thrombotic microangiopathy ( 7 , 8 ), the renal pathology in our patient did not exhibit either of these conditions.…”
Section: Discussioncontrasting
confidence: 65%
“…First, anti-GBM glomerulonephritis has rarely been described as a paraneoplastic disease, but in the reported cases, serum antineutrophil cytoplasmic antibody levels are positive. 12 , 13 Second, there has been a case report of anti-GBM glomerulonephritis associated with nintedanib, 14 but not with bevacizumab. Whereas nintedanib is a small molecule that targets vascular endothelial growth factor receptors-1,2,3, platelet-derived growth factor receptors-α/β, and fibroblast growth factor receptors-1,2,3 pathways, bevacizumab is a recombinant humanized monoclonal antibody that binds to vascular endothelial growth factor-A.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies reported that the treatment effect of tamoxifen on MGN [27]. In addition, a previous study suggests that nintedanib may be a potential trigger for MGN [28]. Nintedanib is a multiple tyrosine kinase inhibitor that works on key angiogenesis pathways including platelet-derived growth factor, vascular endothelial growth factor, and basic fibroblast growth factor.…”
Section: Identification Of Novel Drug Repurposing Candidates For Mgn mentioning
confidence: 99%